Determination of genetic diversity between natural and cultured populations of Common Dentex (Dentex dentex) fish in the East Aegean Sea - Kayaci Ali; Can Mehmet Fatih; Güner Yusuf; Güleç Fatih (Oceanological and Hydrobiological Studies)
Common dentex (Dentex dentex) is a commercial species of fish that is a highly valuable food source living naturally near Mediterranean and Atlantic Coasts. Therefore, monitoring and maintaining common dentex habitats are of high importance. A total of 53 specimens were collected from 6 natural habitats (from the Eastern Aegean and from the Antalya coast, which is the closest coast to the Western Mediterranean), and one aquaculture facility in the Eastern Aegean Sea. The mitochondrial Cytochrome Oxidase I (COI) gene was used to detect a total of 26 haplotypes. Along with the COI gene sequence, real-time PCR and high-resolution melting analyses were performed as rapid and inexpensive alternatives. Sequence analysis showed that the highest haplotype diversity was obtained from the aquaculture facility in Karaburun and Antalya Locations, Turkey. Analysis of Molecular Variance (AMOVA)based on the haplotype frequencies resulted in 92.54% genetic variation within localities and 7.46% genetic variation between/among localities. The mean fixation index (Fst) was calculated as 0.0746 (p < 0.001). Genetic distances were primarily in collaboration with geographical distances and were efficiently confirmed by high resolution melting (HRM) analysis. The results will be valuable in monitoring and maintaining natural habitats as well as aquaculture facilities where common dentex are grown.